The racialized death-politics of urban resilience governance. (2nd January 2019) - Gressgård, Randi
ABSTRACT: In the essay, 'Necropolitics', Achille Mbembe attends to the contemporary subjugation of life to the power of death – exceptional violence that exceeds the biopolitical aim of fostering life – thus alluding to a state of emergency in which law is suspended and martial rule is brought into force. However, as several commentators have suggested, exceptional politics does not need to be legitimized by a declared state of emergency, such as in cases where governmental and non-governmental actors are vested with powers to take strong measures against specific urban sub-populations in the name of security or order maintenance. Still, even these reworked and expanded approaches to death-politics revolve around sovereign exceptionality and the accompanying fabrication of undesirable 'others'. Somewhat counterintuitively, the present article advances an analysis of racialized security politics issuing from the breakdown of representational, topographical boundaries between 'inside' and 'outside', 'us' and 'others'. Illustrated by a case from Malmö, Sweden, it urges greater attention to how necropolitics could operate entirely outside the trope of emergency as exception. The principal argument is that urban security politics, when operating within the frame of resilience governance, involves distinctly different configurations of necropolitics, which require a critical-theoretical vocabulary outside the traditional framework of securitization.